2015
DOI: 10.5465/amr.2013.0273
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Approach to Time and Organizational Change

Abstract: Prevailing perspectives on time and change often emphasize the forward movement of time and the relative stability of attributes, an emphasis that fosters theories of organizational evolution as a linear progression of a past that moves to the present that moves to the future. While useful in many respects, this perspective obscures the uncertainty of emerging organizational phenomena, and it offers little insight into the rare and unpredictable events that change the course of history. To address these concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 109 publications
0
106
0
Order By: Relevance
“…Second, our findings regarding abductive search may open an avenue for new perspectives on searching and strategizing, in light of recent conceptual (Lord et al, 2015;Reetz & MacAulay, 2016) and empirical (Kaplan & Orlikowski, 2012) work in this space.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 80%
“…Second, our findings regarding abductive search may open an avenue for new perspectives on searching and strategizing, in light of recent conceptual (Lord et al, 2015;Reetz & MacAulay, 2016) and empirical (Kaplan & Orlikowski, 2012) work in this space.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 80%
“…In addition, focusing on a linear rather than collaborative structure (GAO, 2003) and failing to address and manage emerging organisational changes (Lord et al, 2015) contributes to higher SCR. Human errors also increase SCR, with examples provided from highly trained specialties such as pilots (Helmreich, 2000), doctors (Van Den Bos et al, 2011) and pharmacists (Samp et al, 2014).…”
Section: Organisational Design and Behaviourmentioning
confidence: 99%
“…Arévalo and Espinosa (2015) also noted that there are hardly any analytical models available for guidance; only some metaphoric and simulation studies can be found in literature. Another theoretical approach, equally interesting, was reported by Lord, Dinh, and Hoffman (2015). The authors provide an organizational theory from the perspective of quantum mechanics and study organizational change.…”
Section: Complexity Management and Decision Makingmentioning
confidence: 99%